2013
DOI: 10.1002/chem.201302306
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia‐Annealed TiO2 as a Negative Electrode Material in Li‐Ion Batteries: N Doping or Oxygen Deficiency?

Abstract: Improving the chemical diffusion of Li ions in anatase TiO2 is essential to enhance its rate capability as a negative electrode for Li-ion batteries. Ammonia annealing has been used to improve the rate capability of Li4 Ti5 O12 . Similarly, ammonia annealing improves the Li-ion storage performance of anatase TiO2 in terms of the stability upon cycling and the C-rate capability. In order to distinguish whether N doping or oxygen deficiencies, both introduced upon ammonia annealing, are more relevant for the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…[33] Increasing the amount of Cu results in increased electron mobility, but it decreases Li-ion mobility. [34] If the addition amount is below 0.05, the enhancement in the electrical conductivity out-weighs the reduction in ion mobility, and therefore, excellent electrochemical performance is exhibited. At a certain point, ion mobility starts to outweigh electron mobility, and the performance begins to decay; this corresponds to LTO + 0.1 Cu and LTO + 0.15 Cu.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…[33] Increasing the amount of Cu results in increased electron mobility, but it decreases Li-ion mobility. [34] If the addition amount is below 0.05, the enhancement in the electrical conductivity out-weighs the reduction in ion mobility, and therefore, excellent electrochemical performance is exhibited. At a certain point, ion mobility starts to outweigh electron mobility, and the performance begins to decay; this corresponds to LTO + 0.1 Cu and LTO + 0.15 Cu.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…However, it leads to a lower specific energy of the battery. The main drawback of titania materials, which is limiting its electrochemical performance, is the low electrical conductivity, which has been addressed by using carbon additives [4,5] or doping [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the CNT-TiO2−δ composites, the covering of TiO2 by CNTs leads to an additional loss of accessible surface area. XRD patterns shown in Figure 2 revealed that the pure anatase phase is present in oxygen-deficient TiO2−δ and all of the CNT-TiO2−δ composites [24]. Clear CNT diffraction peaks were not observed in any of the CNT-TiO2−δ composites, probably due to the insufficiently crystalline structure of the CNTs synthesized at relatively low temperature.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%